Pengaruh Knowledge Management, Entrepreneurial Orientation terhadap Keberhasilan Usaha Warung Makan Ramesan di Kota Salatiga - Rahmasari, Septia Fira; Sirine, Hani (Universitas Batanghari Jambi, 2024)
In a business, business success is something that needs to be considered because it is important for business people and is directly related to the economy of society as a whole. The aim of this research is to examine the influence of knowledge management and entrepreneurial orientation on the success of the Ramesan food stall MSME business in the city of Salatiga. The research is quantitative and uses descriptive research. The population is 80 SME business people in Ramesan food stalls around the city of Salatiga. The number of samples used in this research is the same as the population sampled through purposive sampling, and has been selected based on criteria. Data collection was carried out by distributing questionnaires. The research results reveal that the variables knowledge management and entrepreneurial orientations partially have a positive effect on the success of the Ramesan Food Stall business in Salatiga City. This page is in English Translate to Indonesian AfrikaansAlbanianAmharicArabicArmenianAzerbaijaniBengaliBulgarianCatalanCroatianCzechDanishDutchEnglishEstonianFinnishFrenchGermanGreekGujaratiHaitian CreoleHebrewHindiHungarianIcelandicIndonesianItalianJapaneseKannadaKazakhKhmerKoreanKurdish (Kurmanji)LaoLatvianLithuanianMalagasyMalayMalayalamMalteseMaoriMarathiMyanmar (Burmese)NepaliNorwegianPashtoPersianPolishPortuguesePunjabiRomanianRussianSamoanSimplified ChineseSlovakSlovenianSpanishSwedishTamilTeluguThaiTraditional ChineseTurkishUkrainianUrduVietnameseWelsh Always translate English to IndonesianPRO Never translate English Never translate ekonomis.unbari.ac.idTRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian // TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//